-5(y-6)=5

Simple and best practice solution for -5(y-6)=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(y-6)=5 equation:


Simplifying
-5(y + -6) = 5

Reorder the terms:
-5(-6 + y) = 5
(-6 * -5 + y * -5) = 5
(30 + -5y) = 5

Solving
30 + -5y = 5

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-30' to each side of the equation.
30 + -30 + -5y = 5 + -30

Combine like terms: 30 + -30 = 0
0 + -5y = 5 + -30
-5y = 5 + -30

Combine like terms: 5 + -30 = -25
-5y = -25

Divide each side by '-5'.
y = 5

Simplifying
y = 5

See similar equations:

| 3t(t+5)-t^2=2t^2+4t-1 | | 40r^3+5r^2-8r-1=0 | | 48x^3+40x^2-18x-15=0 | | -225=-x^2 | | 45x=7 | | a^2+13ab+40b^2=0 | | u^2-7uv-18v^2=0 | | 2n-6=3n | | 5a^2-31a+6=0 | | -x-1=-1 | | 16(x-a)=4(2a-x) | | 6+6/64= | | 3+3a=3(1+3a)-6a | | 5n^2-3n-8=0 | | 14=2(x+2) | | 13-10x=109-31x | | 16x^2+12x-25=0 | | 79-4x=41x+24 | | 12(3x+3)-7(2*-2)=12x-10 | | y-y=-2x+4x-1+(-5) | | 8x-12=29x-42 | | 9b=7b-70 | | -5*0= | | 15-y=51 | | 12-8x=42+-29x | | x+4x(4x+32)=12 | | x^2+4-2x=0 | | 8n-12n= | | 39=-2(22-m)+3(m-4) | | 8x-1=5x+20 | | 6(2x-4)=(4x-6) | | 7x^3-21x^2-91x+104=0 |

Equations solver categories